Evolutionary economics and environmental policy survival of the greenest - Bergh, Jeroen C. J. M. van den, 1965-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
This study offers a unique evolutionary economics perspective on energy and innovation policies in the wider context of the transition to sustainable development.
1. Introduction -- 2. Evolutionary economics -- 3. Environmental policy and transition management from an evolutionary perspective -- 4. Evolutionary policy for energy innovations -- 5. Case studies -- 6. Summary and conclusions.
"This book is the result of a joint effort of the Netherlands Environmental Assessment Agency, the Faculty of Economics and Business Administration of the Free University (Vrije Universiteit) in Amsterdam, and the university's Institute for Environmental Studies"--preface.
Includes bibliographical references (p. 154-166) and index.
Keywords: Energy policy -- Netherlands -- Case studies; Energy policy -- Environmental aspects; Evolutionary economics; Environmental policy -- Netherlands; Sustainable development -- Netherlands; Electronic books